Peningkatan Nilai Ekonomis Kelapa melalui Pembuatan Cuka dari Air Kelapa di Desa Morella - Mirella Fonda Maahury; Catherina M. Bijang; Matheis F. J. D. P. Tanasale; Nikmans Hattu; Fensia A. Souhoka; Mario R. Sohilait (Institute for Research and Community Services, 2023)
Vinegar is a seasoning that gives food a sour taste. Vinegar is obtained from the fermentation of ethanol by bacteria anaerobically. Ingredients that can be used to make alcoholic fermentation include dates, rice, and coconut water. Young coconut water is directly consumed, while coconut water from ripe fruit is disposed of as waste. Morella village is located on the coast of the island of Ambon, where coconut plants are in abundance. The abundance of this coconut plant is directly proportional to the old coconut water that is dumped into the environment. To decrease the coconut water waste, it is necessary to conduct training on making vinegar from coconut water for the people of Morella village. This community service was carried out based on counseling and training on making vinegar for the Morella Village people. Counseling was done to convey the benefits of Vinegar and how to make it. The training was carried out by demonstrating the procedure for making vinegar and providing tools and materials to partners and videos to produce vinegar independently. The results of vinegar products from Morella Village are reported to the service team and used as evidence of the success of the vinegar-making training. The results provide information that vinegar are products that the people of Morella village can cultivate as an opportunity to increase their economy.